Optimizing background therapy in treatment-experienced HIV-1 patients by rules-based algorithms and bioinformatics - Svard, J; Sonnerborg, A (Future virology, 2012)
In HIV-1-infected patients with extensive drug resistance, the optimization of background antiretroviral therapy is essential when changing drugs after treatment failure. The genotypic sensitivity score (GSS) and phenotypic sensitivity score (PSS), determined by rules-based algorithms, are employed to predict which drugs to select in a background therapy in order to receive the best treatment response when a new drug will be used, both in investigational trials of new agents and in clinical care. However, the outcome of the GSS/PSS approach for the purpose of assessing antiretroviral efficacy in patients with multiresistance has become more problematic, despite improvements such as drug potency weighting and adding information on treatment history. Bioinformatics-based methods are more recent attractive alternatives that have demonstrated equal or better precision compared with rules-based algorithms. This review aims to discuss the usefulness of GSS/PSS and bioinformatics, respectively, for the optimization of anti-HIV background therapy in heavily treatment-experienced patients.